2022
DOI: 10.3389/fimmu.2022.903564
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer-Infiltrating Regulatory T Cells: Functional Heterogeneity, Metabolic Adaptation, and Therapeutic Targeting

Abstract: Colorectal cancer (CRC) is a heterogeneous disease with one of the highest rates of incidence and mortality among cancers worldwide. Understanding the CRC tumor microenvironment (TME) is essential to improve diagnosis and treatment. Within the CRC TME, tumor-infiltrating lymphocytes (TILs) consist of a heterogeneous mixture of adaptive immune cells composed of mainly anti-tumor effector T cells (CD4+ and CD8+ subpopulations), and suppressive regulatory CD4+ T (Treg) cells. The balance between these two populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 281 publications
(342 reference statements)
0
35
0
Order By: Relevance
“…Immune exhaustion with high levels of expression of PD-L1 and LAG-3 correlates with a shorter OS in CRC patients, 44 and accumulation of Tregs has been associated with CRC progression and metastasis, immunotherapy failure and a poorer prognosis. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune exhaustion with high levels of expression of PD-L1 and LAG-3 correlates with a shorter OS in CRC patients, 44 and accumulation of Tregs has been associated with CRC progression and metastasis, immunotherapy failure and a poorer prognosis. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Immune exhaustion with high levels of expression of PD-L1 and LAG-3 correlates with a shorter OS in CRC patients, 44 and accumulation of Tregs has been associated with CRC progression and metastasis, immunotherapy failure and a poorer prognosis. 45 So far, the role of IL30 in colorectal tumorigenesis has never been explored. Here, we provide evidence that IL30 expressed, as membrane-anchored cytokine, in both stem and non-stem CRC cells, regulates their viability, immunophenotype and tumor progression programs.…”
Section: Open Accessmentioning
confidence: 99%
“…While Th17 and Th22 cells directly promote tumor progression through the release of tumor-promoting cytokines such as IL-17A or IL-17, Tregs suppress the anti-tumor effector response of Th1 cells and cytotoxic CD8 T cells. However, data shedding light on the role of individual Treg subtypes in CRC revealed that this is not always the case (for review, see [ 55 ]). For instance, CD4 + CD25 + Tregs have been shown to suppress inflammation-associated CRC development through the release of IL-10 [ 56 ], and induce CRC regression in the Apcmin/+ mouse model of CRC by regulating the homeostasis of epithelial cells [ 57 ].…”
Section: Tgfβ As a Regulator Of The Tumor Microenvironment In Crcmentioning
confidence: 99%
“…The components of TIICs in the tumor microenvironment (TME) even influence the drug sensitivity and prognosis of cancer 5 . Regulatory T cells (Tregs) are an important subtype of TIICs with two‐sided roles in the context of CRC 6 . On the one hand, an abundance of Tregs can inhibit the activity of effector T cells, particularly cytotoxic T cells, creating a sanctuary that shields cancer cells from immune recognition and elimination 7 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Regulatory T cells (Tregs) are an important subtype of TIICs with two-sided roles in the context of CRC. 6 On the one hand, an abundance of Tregs can inhibit the activity of effector T cells, particularly cytotoxic T cells, creating a sanctuary that shields cancer cells from immune recognition and elimination. 7 Through the secretion of pro-angiogenic factors, Tregs facilitate the formation of new blood vessels, ensuring the nutrient supply for sustained tumor development.…”
mentioning
confidence: 99%